2021
DOI: 10.1002/anie.202015249
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective and Redox‐Neutral Cp*IrIII‐Catalyzed Allylic C−H Alkynylation

Abstract: Herein, we report a Cp*IrIII‐catalyzed highly regioselective and redox‐neutral protocol for the construction of 1,4‐enynes from unactivated olefins and bromoalkynes via intermolecular allylic C−H alkynylation. The developed mild reaction conditions tolerate a broad range of common functional groups, even enabling selective alkynylation of allylic C−H bonds in the presence of other prominent directing groups. Mechanistic experiments including the isolation of a catalytically active IrIII‐allyl species support a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 75 publications
(27 reference statements)
1
3
0
1
Order By: Relevance
“…Here we report the Rh-catalysed nitro-directed C–H alkynylation of nitrobenzenes, which tolerates a broad range of functional groups ( Scheme 1c ). 11 Our experimental and computational mechanistic investigations are consistent with a turnover limiting electrophilic C–H activation step, followed by alkyne insertion and bromide elimination. We also disclose preliminary results on a related C–H iodination reaction, which may pave the way for other types of ortho -functionalization via sequential Rh/Pd catalysis.…”
Section: Introductionsupporting
confidence: 74%
“…Here we report the Rh-catalysed nitro-directed C–H alkynylation of nitrobenzenes, which tolerates a broad range of functional groups ( Scheme 1c ). 11 Our experimental and computational mechanistic investigations are consistent with a turnover limiting electrophilic C–H activation step, followed by alkyne insertion and bromide elimination. We also disclose preliminary results on a related C–H iodination reaction, which may pave the way for other types of ortho -functionalization via sequential Rh/Pd catalysis.…”
Section: Introductionsupporting
confidence: 74%
“…Alkenes are important feedstocks in synthetic chemistry due to their versatility; they are inherently nucleophilic but can easily be made electrophilic by the addition of certain functional groups or catalysts. Alkenes can also serve as activating groups for adjacent C–H bonds, allowing even greater synthetic utility. One of the biggest challenges for alkene functionalization is to achieve regioselectivity. While this is easily overcome for terminal olefins and cyclization reactions, , internal alkenes often undergo poor regiochemically selective reactions without the aid of activating functional groups. This has spawned a significant research enterprise exploring how to achieve regioselective transformations in electronically unbiased alkenes. For transition metal-catalyzed reactions, one of the most effective strategies has been the use of directing groups (DGs).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above-described research and other studies, − , we speculated that adding a weakly coordinated fluorine-containing anion like BF 4 – , PF 6 – , or SbF 6 – to a fluorinated alcohol could further stabilize electron-deficient reaction intermediates. However, we found that using these anions in common organic solvents such as dichloromethane does not promote polycyclization reactions.…”
Section: Introductionmentioning
confidence: 74%
“…In our previous studies , and in studies by other research groups, the effects of adding a BF 4 – , PF 6 – , or SbF 6 – salt to a fluorinated alcohol reaction medium were compared; in most cases, all three anions were found to enhance the yields of the reactions studied. However, there was no consistent pattern in the yield enhancement between reactions.…”
Section: Resultsmentioning
confidence: 99%